A Print Crisis or a Local Crisis?: Local news use over three decades. (1st February 2017) - Wadbring, Ingela; Bergström, Annika
Abstract : Local news is a crucial source of information, as well as a force for cohesion and an arena for debate in local societies. Consequently, it is important to reveal the transformation processes happening among local news audiences. All Western countries are facing a newspaper crisis. It is not, however, entirely obvious whether the crisis is a business model crisis for newspapers in general or only a local news crisis. Our aim is to analyse the consumption of newspapers and other local news media in the light of generational changes, through an annual, longitudinal survey conducted since 1986. The findings indicate that there is neither a print crisis, nor a local crisis, but a general newspaper crisis. The readership for both print and online newspapers is decreasing even as local broadcast news exhibits a rather more stable audience. Free daily newspapers seem to have faced the same kind of challenge as the paid-for daily newspapers, but the critical turning point occurred later and for different reasons. When analysing the transformation processes from a generational perspective, it is evident that the youngest generation in our society is abandoning newspapers, regardless of the form in which they are published, and the rate of decline has increased.